Sonogenetics: a mini review - Bell, Kama; Heo, Hyeonu; Jing, Yun (Frontiers in Acoustics, 2023)
Sonogenetics has emerged as a tool of therapeutic ultrasound which is revolutionizing the ability to non-invasively modulate the activity of neurons and other excitatory cells. This technology utilizes bioengineering methods to confer or amplify ultrasound sensitivity in target cells using engineered or modified protein mediators. The neuromodulation community has shown a growing interest in sonogenetics due to ultrasound's ability to penetrate the skull and reach deep brain tissue, enabling non-invasive modulation of neurons. Novel methods of sonogenetics aim to enhance cellular control in humans by leveraging mechanosensitive and thermosensitive cellular mechanisms activated by ultrasound to address cellular dysfunction and degeneration. This mini review summarizes the progress of sonogenetic mediators proposed for neuromodulation and looks at new therapeutic applications of sonogenetics for cancer treatment and vision restoration.